GSTT1/GSTM1 deficiency aggravated cisplatin-induced acute kidney injury via ROS-triggered ferroptosis - Li, Peipei; Li, Duopin; Lu, Yanfang; Pan, Shaokang; Cheng, Fei; Li, Shen; Zhang, Xiaonan; Huo, Jinling; Liu, Dongwei; Liu, Zhangsuo (Frontiers in Immunology, 2024)
Cisplatin is a widely used chemotherapeutic agent prescribed to treat solid tumors. However, its clinical application is limited because of cisplatin-induced nephrotoxicity. A known complication of cisplatin is acute kidney injury (AKI).Deletion polymorphisms of GSTM1 and GSTT1, members of the glutathione Stransferase family, are common in humans and are presumed to be associated with various kidney diseases. However, the specific roles and mechanisms of GSTM1 and GSTT1 in cisplatin induced AKI remain unclear. Here, we found that GSTT1 and GSTM1 were downregulated in the renal tubular cells of AKI patients and cisplatintreated mice. Compared with WT mice, Gstm1/Gstt1-DKO mice were phenotypically normal but developed more severe kidney dysfunction and exhibited increased ROS levels and severe ferroptosis after injecting cisplatin. Thus, our study revealed that GSTM1 and GSTT1 can protect renal tubular cells against cisplatin-induced nephrotoxicity and ferroptosis, and genetic screening for GSTM1 and GSTT1 polymorphisms can help determine a standard cisplatin dose for cancer patients undergoing chemotherapy.